Comparative Study on the Adsorption Kinetics and Thermodynamics of Metal Ions onto Acid Activated Low Cost Pandanus Carbon - R. Sudha; K. Kalpana; T. Rajachandrasekar; S. Arivoli (E-Journal of Chemistry)
Batch experiments were carried out for the sorption of Copper and Ferrous ions onto acid activated carbon prepared. The operating variables studied were initial metal ion concentration, pH, and temperature and contact time. The equilibrium data were fitted to the Langmuir and Freundlich isotherm equations. From this adsorption efficiency, adsorption energy, adsorption capacity, intensity of adsorption and dimensionless separation factor were calculated. From the kinetic studies the rate constant values for the adsorption process was calculated. From the effect of temperature thermodynamic parameters like ΔG°, ΔH°, and ΔS° were calculated. The mechanism of adsorption for metal ions onto carbon was investigated by using the experimental results and confirmed by FT- IR, XRD and SEM images.